Answer:
1) 23; -8; 19; 73; 4; -76; 61; -6
10g - 40; 7y + 21; -12w + 9; 6r+3
2) -4x +8; 18w -3z -7; 15n - 41; 17x+10y; -75 - 63d; 12b-9; 0; 6h -39
Explanation:
a = 9, b = -3, c = -2, d = 7
1. a -cd = 9 - (-2)(7)
= 9 + 14 = 23
2. 2b+ c = 2(-3) + (-2)
= -6 -2 = -8
3. 2a+d−cb = 2(9) + 7 -(-2)(-3)
= 18 +7 -(6) = 25-6 = 19
4. (a–b)2+ d(a + c) = (9-(-3))*2 + 7(9+(-2))
= (9+3)*2 + 7(9-2) = 12*2 + 7(7)
= 24 + 49 = 73
5. 4c –(b –a) = 4(-2) - (-3 -9)
= -8 - (-12) = -8+12 = 4
6. ab-5a = 9(-3) - 5(9)
= -27 -49 = -76
7. 2bc+ d(12 –5) = 2(-3)(-2) + 7(12-5)
= 2(6) + 7(7) = 12 + 49 = 61
8. b + 0.5[8 –(2c + 2a)]
= -3 + 0.5[8-(2*-2 + 2*9)]
= -3 + 0.5(8-(-4+18)) = -3+0.5(8-14)
= -3+0.5(-6) = -3-3 = -6
Using Distributive Property
9. 5(2g –8) = 5*2g - 5*8
= 10g - 40
10. 7(y + 3) = 7*y + 7*3
= 7y + 21
11. -3(4w–3) = -3*4w -3(-3)
= -12w + 9
12. (6r + 3) = 1(6r + 3)
= 1*6r + 1*3
= 6r + 3
2) Simplify each expression
13. 8(x + 1) –12x = 8x + 8 -12x
= 8x -12x + 8 = -4x +8
14. 6w –7 + 12w –3z
= 6w+12w –3z –7
= 18w -3z -7
15. 9n –8 + 3(2n –11)
= 9n -8 +6n -33 = 15n - 41
16. 3(7x + 4y) –2(2x + y)
= 21x +12y -4x-2y = 21x -4x +12y-2y
= 17x + 10y
17. (15+ 8d)(-5) –24d + d
= -5(15) -5(8d) -24d + d
= -75 -40d -24d +d
= -75 - 63d
18. 9(b –1) –c + 3b + c
= 9b -9 -c +3b +c = 9b +3b -c +c -9
= 12b -9
19. 20f–4(5f + 4) + 16
= 20f -20f -16 +16 = 0
20. 8(h –4) –h–(h + 7)
= 8h - 32 -h -h -7
= 8h -2h -32-7
= 6h -39